Anterior cervical discectomy and fusion to treat cervical instability with vertigo and dizziness: A single center, retrospective, observational study - Zheng, Huo-Liang; Li, Bo; Song, Shao-Kuan; Chen, Peng-Bo; Jiang, Lei-Sheng; Jiang, Sheng-Dan (Frontiers in Surgery, 2023)
Purpose: The current study attempts to investigate the role of anterior cervical discectomy and fusion (ACDF) in alleviating symptoms in patients with cervical vertigo associated with cervical instability. Methods: The patients of cervical instability with vertigo and dizziness who underwent ACDF between January 2011 and December 2019 were followed-up for more than two years. Symptoms of vertigo and dizziness before and after surgery were assessed by the 15-item version of the Vertigo Symptom Scale (VSS) and the 25-item Dizziness Handicap Inventory (DHI). The severity of other symptoms like neck and occipital pain, gastrointestinal discomfort, nausea, vomiting, tinnitus, palpitations, hypertension, headache, diplopia and blurring of vision before and after surgery were also assessed. Results: A total of 92 patients underwent ACDF for cervical instability with vertigo and dizziness, of which 79 patients were included in the final analysis. Patients with C3/4 instability suffered a severer vertigo than other levels. Both DHI and VSS scores were significantly reduced after ACDF and this was sustained within two years after surgery (p < 0.001). Although there was no statistical difference in the ratio of patients with vertigo relief, one-level ACDF resulted in faster vertigo improvement than multi-level ACDF (p=0.048). Also, there was improvement in most accompanying symptoms after surgery. Conclusions: Vertigo caused by C3/4 instability was severer than other levels. During 2 years’ follow-up the significant relief of vertigo and dizziness was observed after anterior cervical surgery. Other accompanying symptoms except hypomnesia and hypertension were also extenuated in follow-up period.